(untitled) (Tempo e Argumento, 2023)
This paper aimed to problematize, through Guarani perspectives, some of the rationalities that support the binaries of colonization, such as those that divide ethnocide and genocide, human and animal, savage and civilized, time and eternity. Recognizing that colonial violence is not a finished process, the article seeks to contribute to a diagnosis of the actualization of these violences, at the same time as it seeks to share some of the Guarani resistance to the same process. Based on qualitative research in undergraduate thesis by academics from the Guarani people trained in the Intercultural Indigenous Degree Course of the South of the Atlantic Forest at the Federal University of Santa Catarina (UFSC), the article presents Guarani perspectives on colonization, its effects and forms of resistance. As a result, the research highlights the importance of indigenous perspectives being increasingly recognized as valid epistemologies for thinking about and combating racism and ethnogenocide, as, in addition to diagnosing colonial violence, they also point out clues for the reforestation of the imaginary, not only for indigenous peoples, but for all other beings.